Manajemen Mutu Pembelajaran Pendidikan Agama Islam SMA Muhammadiyah Pohgading - Shanti Ariani, Sri (Lembaga Bale Literasi, 2025)
The quality of Islamic religious education plays a crucial role in shaping students' personalities. The purpose of this study is to examine the quality management of Islamic religious education. This study aims to understand the planning, implementation, and evaluation of Islamic Religious Education (PAI) quality management at SMAS Muhammadiyah Pohgading Boarding School. The method used was qualitative analysis with a case study approach in Aqidah at SMA Muhammadiyah Pohgading. Data collection was conducted through observation, interviews, and documentation. The informants in this study were the Islamic Religious Education teacher, the principal, and the vice principal in Aqidah at SMA Muhammadiyah Pohgading. The data obtained were then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate: 1) The quality planning of learning at SMA Muhammadiyah Pohgading has been implemented quite well. Evidence of this good planning is that the planning prior to PAI learning is sufficiently structured, with the creation of lesson plans (RPPs) used by teachers to structure the lessons. 2) The implementation of quality management in learning has been quite well implemented. This is indicated by the RPP that can be implemented according to what is written there. Supported by a variety of learning models, methods that encourage students to be active in learning. 3). Evaluation of learning quality Evaluation of student learning outcomes is carried out in the form of joint work meetings. In measuring the success of learning by evaluating learning outcomes in several ways, namely: daily tests, semester exams, evaluation by looking at daily grades obtained by students and also seen from 3 aspects, attitude assessment, knowledge.